2018
DOI: 10.1080/19490976.2018.1526581
|View full text |Cite|
|
Sign up to set email alerts
|

Immobilization of cadmium and lead by Lactobacillus rhamnosus GR-1 mitigates apical-to-basolateral heavy metal translocation in a Caco-2 model of the intestinal epithelium

Abstract: Heavy metals are highly toxic elements that contaminate the global food supply and affect human and wildlife health. Purification technologies are often too expensive or not practically applicable for large-scale implementation, especially in impoverished nations where heavy metal contamination is widespread. Lactobacillus rhamnosus GR-1 (LGR-1) was shown in previous work to reduce heavy metal bioaccumulation in a Tanzanian cohort of women and children through indeterminant mechanisms. Here, it was hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 52 publications
5
58
0
1
Order By: Relevance
“…Previous studies have examined the effects of cadmium on the microbes associated with mice (76) and spiders (44) and the effects of selenate on bumble bee microbes (35). Host-associated microbes can detoxify or sequester toxic metals, including arsenic (47), selenate (35), lead and chromium (48), copper (49), and cadmium (50)(51)(52). Our research extends this work by showing that bee-associated microbes can be affected by metal(loid) exposure and are able to bioaccumulate some of these compounds and that the metabolome is changed in response to selenate and cadmium poisoning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have examined the effects of cadmium on the microbes associated with mice (76) and spiders (44) and the effects of selenate on bumble bee microbes (35). Host-associated microbes can detoxify or sequester toxic metals, including arsenic (47), selenate (35), lead and chromium (48), copper (49), and cadmium (50)(51)(52). Our research extends this work by showing that bee-associated microbes can be affected by metal(loid) exposure and are able to bioaccumulate some of these compounds and that the metabolome is changed in response to selenate and cadmium poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…As many of the honey bee gut microbes were resilient to metal or metalloid challenge, we next determined whether common bee-associated bacteria can remove these toxicants from their immediate environment. The potential for bacteria to protect their host from toxic metal exposure through bioaccumulation is an emerging topic of investigation in several systems, including humans (51,85), mice (49,52), and insects (48). We exposed strains of bee-associated bacteria to cadmium in vitro and found that all assayed taxa removed a significant amount of cadmium from their growth media after 2 days of incubation.…”
Section: Toxicants Affect the Bee Microbiome And Metabolomementioning
confidence: 99%
See 1 more Smart Citation
“…One potential explanation for the association with desirable cardiometabolic and psychological scores observed in our study for yogurt or milk is the production of metabolites such as folate and GABA by S. thermophilus , Bifidobacterium and Lactobacillus 90, 91 . Moreover, Lactobacilli have been reported to sequester heavy metals including lead and cadmium 92 . All of these live or dead probiotics could potentially exert functions on the immune system or even the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Pb absorption and immobilization reducing its translocation across the intestinal epithelium in vitro Daisley et al, 2019…”
mentioning
confidence: 99%